President of the Republic Decree No. 330 Of The Year 2015 Concerning the Establishment of Suez Canal Economic Zone = قرار رئيس جمهورية مصر العربية رقم 330 لسنة 2015 بإنشاء المنطقة الإقتصادية لقناة السويس - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic